PENGARUH PENGGUNAAN BIOSUPLEMEN MENGANDUNG BAKTERI PROBIOTIK SELULOLITIK ASAL RAYAP (Termites sp.) TERHADAP PRODUKTIVITAS ITIK BALI JANTAN - M. P., LAKSMI DEWI; SUTAMA, N. S.; DEWI, G. A. M KRISTINA (Majalah Ilmiah Peternakan; Vol 21 No 1 (2018): Vol 21, No 1 (2018), 2018)
The research aims at analyzing the effect use of probiotic cellulolytic biosuplement termite (Termites sp.) to the productivity of male bali ducks. Bacteria isolates used were first and second preeminent probiotic cellulolytic bacteria isolated derived from termites code BR3.3 and BR3.5. It was designed using a Completely Randomized Design with five treatments and three replicates consists of: basal ration without biosuplement (R0), ration basal with biosupplement but without additional probiotic cellulolytic bacteria inoculant preeminent termites (RBCT0), RBCT1= basal ration with biosuplement probiotic cellulolytic bacteria inoculant preeminent termites 1, RBCT2= basal ration with biosuplement probiotic cellulolytic bacteria inoculant preeminent termites 2 and RBCT1-2= basal ration with biosuplement probiotic cellulolytic bacteria inoculant preeminent termites 1 and 2. The result showed that the initial body weight, slaughter weight and carcass percentage had no significant differences (P>0.05). In contrast, final body weight, body weight gain, feed consumption, Feed Conversion Ratio and meat total cholesterol were significantly affected (P<0,05) to the result. It can be concluded that use of basal ration supplemented with biosupplement probiotic cellulolytic bacteria inoculant preeminent termites 2 (RBCT2) can increase productivity of bali duck at the age of 2 up to10 weeks.